Editor’s note: We proudly offer you the third issue of the Journal of New Librarianship - Stephen Weiter (Journal of New Librarianship, 2017)
This open journal is the result of collaborative efforts among colleagues within the field of library and information sciences. With this issue we introduce topical columns to the content of the journal. Additionally, with this, our third issue, we are moving to a rolling publishing schedule so that we can bring you more outstanding content in a timely matter. We are committed to publishing a multitude of viewpoints, encouraging dialog, and at times, provoking our readers to think and respond.